DNA barcoding of morphologically characterized mosquitoes belonging to the subfamily Culicinae from Sri Lanka - Weeraratne, T.C.; Surendran, S.N.; Karunaratne, S.H.P.P. (University of Jaffna, 2018)
: Vectors of mosquito-borne diseases in Sri Lanka, except for malaria, belong to the subfamily Culicinae, which includes nearly 84% of the mosquito fauna of the country. Hence, accurate and precise species identification of culicine mosquitoes is a crucial factor in implementing effective vector control strategies. During the present study, a combined effort using morphology and DNA barcoding was made to characterize mosquitoes of the subfamily Culicinae for the first time from nine districts of Sri Lanka. Cytochrome c oxidase subunit 1 (cox1) gene from the mitochondrial genome and the internal transcribed spacer 2 (ITS2) region from the nuclear ribosomal DNA were used for molecular characterization.
Keywords: DNA barcoding; culicinae; Mosquitoes; aedes; culex; sri lanka; cox1; ITS2